Nutritional properties of common bean protein concentrate compared to commercial legume ingredients for the plant-based market - Lucas de Paiva Gouvêa; Rodrigo Fernandes Caldeira; Tatiana de Lima Azevedo; Rosemar Antoniassi; Melicia Cintia Galdeano; Ilana Felberg; Janice Ribeiro Lima; Caroline Grassi Mellinger (Current Research in Food Science)
There is an enormous demand to develop new sources of proteins, mainly to supply the growing plant-based food market worldwide, with the push for more sustainable and healthier products. The objective of this study was to evaluate the composition and the nutritional properties of commercial soybean, pea, and fava bean protein ingredients and compare them with an in-house ingredient (flour and protein concentrate), obtained from the main Brazilian cultivar of common bean (Phaseolus vulgaris, Pinto bean). The protein content of the common bean concentrate (79.75%) was as high as other commercial proteins isolated from the pea and higher than the others concentrates. All the ingredients presented the minimum amounts of indispensable amino acids as required by FAO and all ingredients were rich in lysine and leucine, with the highest amounts found for pea (78.06 mg/g) and common bean (86.70 mg/g) concentrates. A diverse mineral composition was reported for all the ingredients and the common bean concentrate presented the highest iron content (342.6 mg/kg). In terms of antinutritional factors, the common bean flour and concentrate showed the highest values for trypsin inhibitor (18 and 27 TIU/mg, respectively) but the lowest ones for phytic acid (9 and 2 mg/g, respectively) compared to the other ingredients. Low amounts of oligosaccharides were found in most of the samples. All proteins from the ingredients were highly digested when evaluated in vitro, but phaseolins fraction protein from common bean samples remained partially undigested. Despite compositional differences between ingredients, all samples should be suitable as protein sources for plant-based food innovation.